Compensação tributária: análise do processo de causalidade jurídica para fins de extinção da obrigação jurídica tributária - Janini, Tiago Cappi (2008)
The work s purpose is to analyse the judicial causality of the rules of law included in the tax compensation. Describe the rules accomplishment series that will compose the compensation judicial fact, that is, the tax credit formalization and the Treasury debit relation, and the rules that composes the compensation judicial relation. Devote to study the three possible ways to supress the tax obligation under compensation view, in accordance with the individual and concrete rule sender: (i) for the administrative authority; (ii) for the taxpayer; (iii) for the judiciary authority. Use the logic-semantic construction method, approaching the law like a communication process, constituted, modified and extinted only for judicial language. In view of the premise, identify several rules accomplishment series of the tax compensation, always finishing with the individual and concrete rule production whose content is the tax judicial relation s extinction. This study make evident that tax compensation is a complex judicial act, needing several rules accomplishment series to hit yours objective